Kursus Bahasa Inggris Untuk Anak – Anak Di Desa Setiling - Khalik, Abdul; Adrian , Bayu; Sartikawati, Dewi; Fajriah, Hafifatul; Susilawati , Ely; Hidayatullah; Jannah , Miftahul; Rohana , Siti; Sapriatin; Damayanti, Yulia; Sahabudin (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2024)
The English course emphasizes reading and writing. Through interpreting the written word, writing down thoughts and ideas, and receiving feedback, you will naturally improve your vocabulary and grammar skills. Plus, you'll have more words to express yourself clearly and communicate ideas effectively. Developing vocabulary and grammar skills not only helps speaking English. English develops naturally for native speakers. Many people don't understand the rules of formal grammar, but they know when something doesn't sound right to them. However, when you learn the rules of your own language, it can make learning a foreign language easier and more comfortable